Gender Differences in Text‐Based Interest: Text Characteristics as Underlying Variables. Issue 2 (31st May 2021) - Lepper, Chantal; Stang, Justine; McElvany, Nele
ABSTRACT: Reading motivation is a fundamental basis for reading behavior and performance. For learners, interest is an exceedingly important component of reading motivation. Prior research has shown that students' text‐based interest varies significantly between texts. However, it is still unclear why one text elicits greater interest over another. Therefore, in this study, we investigated whether different text characteristics, such as text genre, topic, and protagonists' gender, are systematically related to students' text‐based interest. Furthermore, we examined differences between girls and boys. We used data from a sample of 504 fourth‐grade elementary school students to answer these questions. Eight texts were manipulated experimentally with respect to text genre, topic, and protagonists' gender. Students were assigned randomly to read one of the eight texts. Structural equation models showed that students' text‐based interest was related to text genre, topic, and students' gender. Moreover, students' gender interacted significantly with text topic and protagonists' gender, with boys less interested in texts with a more female‐typed text topic and in texts with female protagonists. The findings imply that text characteristics might help educators select reading material to encourage students' text‐based interest. The results are discussed in terms of research and educational practice.